Calcium Signaling Protocols - Lambert, David G.; Rainbow, Richard D.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
The regulation of intracellular Ca2+ has continued to be a powerful area of study since the publication of the first and second editions of Calcium Signaling Protocols, and the developments in the field have also, naturally, continued.  With the third edition, expert contributors explore some of the exciting new molecular techniques that have both enabled new studies of intracellular Ca2+ regulation and provided much new information on processes.  Comprised of five main section, the book covers theoretical and very simple suspension-based fluorimetric assays, specialist measurement systems, measurement of channel activity, measurement of store release, as well as specialist measurement techniques which include targeted probes, using G-protein chimeras to force Ca2+ signalling for screening, and genetically encoded sensors.  Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Updated and accessible, Calcium Signaling Protocols, Third Edition will be a valuable reference for all those contemplating a move into the study of intracellular Ca2+.
Fluorescent Measurement of [Ca2+]c: Basic Practical Considerations -- Measurement of [Ca2+]i in Whole Cell Suspensions Using Fura-2 -- Confocal Microscopy: Theory and Applications for Cellular Signaling -- Ratiometric Ca2+ Measurements Using the FlexStation® Scanning Fluorometer -- Measuring Ca2+ Changes in Multiwell Format Using the Fluorometric Imaging Plate Reader (FLIPR®) -- Ratiometric [Ca2+]i Measurements in Adherent Cell-lines Using the NOVOstar Microplate Reader -- Whole-Cell Patch Clamp Recording of Voltage-Sensitive Ca2+ Channel Currents in Single Cells: Heterologous Expression Systems and Neurones -- Combined Calcium Fluorescence Recording with Ionic Currents in Contractile Cells -- Measurement of Phospholipase C by Monitoring Inositol Phosphates Using [3H]Inositol Labeling Protocols in Permeabilized Cells -- Single Cell Imaging Techniques for the Real-Time Detection of IP3 in Live Cells -- Measurement of Inositol(1,4,5)Trisphosphate Using a Stereospecific Radioreceptor Mass Assay -- Measurement of [Ca2+]i in Smooth Muscle Strips Using Front-Surface Fluorimetry -- Calcium Measurements from Whole Heart Using Rhod-2.- Measurement of Changes in Endothelial and Smooth Muscle Ca2+ in Pressurized Arteries -- Single Cell and Subcellular Measurements of Intracellular Ca2+ Concentration -- Simultaneous Analysis of Intracellular pH and Ca2+ from Cell Populations -- Measurements of Ca2+ Concentration with Recombinant Targeted Luminescent Probes -- Chimeric G-Proteins in Fluorimetric Calcium Assays: Experience with Opioid Receptors -- Compartmentalizing Genetically-Encoded Calcium Sensors -- Measurement of Cytosolic-Free Ca2+ in Plant Tissue -- Measurement of Ca2+-ATPase Activity (in PMCA and SERCA1).
Keywords: Biochemistry; Biochemistry, general